Generation Z and Its OTT Usage Patterns: The Case of Netflix in Korea - Jungah Ahn (International JOURNAL OF CONTENTS, 2022)
This study aims to reveal the various differences within the factors that influence use satisfaction, continuous use intention, and media substitution intention, specifically in regard to the use motives and use behaviors of Netflix viewers. This study’s results demonstrate that the following various factors affected use satisfaction, continuous use intention, and media substitution intention in differential ways. Firstly, the diversity of content influenced use satisfaction to a greater degree than social relations; and the diversity of content, social relations, and active participation all positively influenced continuous use intention. In other words, the more positively users appreciated the diversity of content, and the more strongly they had social relations, and the more actively they participated within communities, the greater degree to which they increased their continuous use intention for Netflix. However, the diversity of content and the convenience of use also had a negative effect on the media substitution intention for Netflix, which means that the more diverse the content and the more convenient the use of Netflix, the fewer the number of users who intended to cancel Netflix and subscribe to another OTT service or resubscribe to traditional media sources. KCI Citation Count: 1